Membudidayakan Lahan Kosong Warga Menjadi Usaha Perkebunan Buah dan Sayur di Kampung Banyu Hidup Tanah Bumbu - Desi, Hidayati (Jambura Arena Pengabdian, 2024)
Banyu Hidup Village, located in Tanah Bumbu Regency, has a lot of empty land that has not been utilized optimally. This community service aims to utilize the empty land into fruit and vegetable plantations in order to improve the economy, food availability and farming skills of the local community. Through training and improving agricultural skills, the community is expected to be able to turn empty land into productive land, which will have a positive impact on the residents' economy. Implementation methods include land surveys, outreach and training in plant cultivation techniques. The results of the activity show an increase in farming skills and residents' motivation to utilize empty land. In addition, planting corn and spinach produced a good harvest within three months, which had a direct impact on increasing residents' income. Survey results show that 80% of residents involved were satisfied and gave positive feedback about this program. The success of this program shows the importance of planning and community participation in optimizing the potential of vacant land for community welfare.